2008
DOI: 10.1111/j.1524-4733.2007.00213.x
|View full text |Cite
|
Sign up to set email alerts
|

Medication Compliance and Persistence: Terminology and Definitions

Abstract: Providing specific definitions for compliance and persistence is important for sound quantitative expressions of patients' drug dosing histories and their explanatory power for clinical and economic events. Adoption of these definitions by health outcomes researchers will provide a consistent framework and lexicon for research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
1,492
2
70

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,878 publications
(1,579 citation statements)
references
References 29 publications
15
1,492
2
70
Order By: Relevance
“…Our epidemiological data were either obtained from statistics provided by national institutions or extrapolated estimates from scientific literature. Our estimates for adherence rates were taken from a number of different studies which could have used definitions different to that given in our study [16]. Likewise, costs were obtained from a number of data sources using methods and definitions which may have varied from one country to the other.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our epidemiological data were either obtained from statistics provided by national institutions or extrapolated estimates from scientific literature. Our estimates for adherence rates were taken from a number of different studies which could have used definitions different to that given in our study [16]. Likewise, costs were obtained from a number of data sources using methods and definitions which may have varied from one country to the other.…”
Section: Discussionmentioning
confidence: 99%
“…Hypertensive patients (BP C 140/90) may or may not be diagnosed with hypertension. The model assumes that all diagnosed patients are treated and that adherence to treatment (defined as the extent to which a patient acts in accordance with the prescribed interval and dose of a dosing regimen [16]) is the main driver for the patient to achieve a controlled blood pressure (BP \ 140/90) and consequently a lower probability of experiencing a cardiovascular event.…”
Section: Modelmentioning
confidence: 99%
“…It can be defined as the extent to which a patient acts in accordance with the prescribed interval and dose of a dosing regimen. Compliance is usually measured over a period of time and reported as a percentage [29]. Compliance differs from persistence, which is defined as the duration of time from initiation to discontinuation of therapy.…”
Section: The Importance Of Compliance Persistence and Adherence For mentioning
confidence: 99%
“…Three systematic reviews have been conducted on oral antineoplastic agents. One review of 12 studies used the most commonly cited definition of adherence in the literature, 'the extent to which a person's behavior coincides with medical or health advice', 14 a second review (n = 22) used the ISPOR definition, 15 while the third (n = 6) concluded that no standard definition of adherence was used across studies and this made comparison of results between studies difficult. 16 Of the 43 studies in the literature, only 24 reported a definition of adherence (See article on assessment and measurement elsewhere in this issue).…”
Section: Operational Definition Of the Health Status Outcome Adherencementioning
confidence: 99%